2009
DOI: 10.1021/ic9011394
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically-Induced TCNQ/Mn[TCNQ]2(H2O)2(TCNQ = 7,7,8,8-Tetracyanoquinodimethane) Solid−Solid Interconversion: Two Voltammetrically Distinct Processes That Allow Selective Generation of Nanofiber or Nanorod Network Morphologies

Abstract: Unlike the case with other divalent transition metal M[TCNQ](2)(H(2)O)(2) (M = Fe, Co, Ni) analogues, the electrochemically induced solid-solid phase interconversion of TCNQ microcrystals (TCNQ = 7,7,8,8-tetracyanoquinodimethane) to Mn[TCNQ](2)(H(2)O)(2) occurs via two voltammetrically distinct, time dependent processes that generate the coordination polymer in nanofiber or rod-like morphologies. Careful manipulation of the voltammetric scan rate, electrolysis time, Mn(2+)((aq)) concentration, and the method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Over the past few decades, significant attention has been directed toward metal–organic semiconducting materials based on charge-transfer complexes of metal-7,7,8,8-tetracyanoquinodimethane (TCNQ), principally investigated by Dunbar, Miller, and Bond. In particular, CuTCNQ has been the subject of intensive research, based on the observation of switching effects from a high to low impedance state upon application of an external electric field or optical excitation. There exists two phases of CuTCNQ, namely phase I, which possesses a higher room-temperature conductivity (0.2 S cm –2 ), with respect to phase II (1 × 10 –5 S cm –2 ). The two phases also differ in morphology: phase I tends to form rodlike structures and phase II typically leads to platelike structures.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, significant attention has been directed toward metal–organic semiconducting materials based on charge-transfer complexes of metal-7,7,8,8-tetracyanoquinodimethane (TCNQ), principally investigated by Dunbar, Miller, and Bond. In particular, CuTCNQ has been the subject of intensive research, based on the observation of switching effects from a high to low impedance state upon application of an external electric field or optical excitation. There exists two phases of CuTCNQ, namely phase I, which possesses a higher room-temperature conductivity (0.2 S cm –2 ), with respect to phase II (1 × 10 –5 S cm –2 ). The two phases also differ in morphology: phase I tends to form rodlike structures and phase II typically leads to platelike structures.…”
Section: Introductionmentioning
confidence: 99%
“…Metal−organic semiconducting materials based on charge transfer complexes of metal-7,7,8,8-tetracyanoquinodimethane (TCNQ) have received considerable attention over the past 40 years, with a particular resurgence in interest in the past few years through the work of Dunbar et al, Miller et al, and Bond et al In particular, CuTCNQ has been the subject of intensive research given the observation of a switching effect from a high to low impedance state upon the application of an electric field or optical excitation. It has also been demonstrated that CuTCNQ can exist in two phases, namely, phase I that has a room temperature conductivity of 0.2 S cm −1 and phase II with a conductivity of 10 −5 S cm −1 . There have been many attempts to synthesize CuTCNQ in various morphologies using chemical, electrochemical, and photochemical techniques; however, to date there has been little or no attempt to modify the surface of CuTCNQ once it has been formed .…”
Section: Introductionmentioning
confidence: 99%
“…As found for TCNQ/M nþ (TCNQ) n solid-solid interconversion reactions (M nþ ¼ Mn 2þ , Fe 2þ , Co 2þ , Ni 2þ , Cu þ or alkali metal cations), [36,[38][39][40][43][44][45]49] (aq) , presumably owing to increasing ohmic drop effects (iR u ). [36,[38][39][40][43][44][45] This effect is also apparent when the scan rate is increased from 5 to 50 mVs À1 (Fig. S6a, (aq) electrolyte concentration over the range of 5 mM to 0.50 M using TCNQmodified GC electrode (mechanical attachment) and a scan rate of 20 mV s À1 is relatively small, ,8 mV shift per decade change in concentration as shown in Fig.…”
Section: Uv-vis Spectroscopymentioning
confidence: 81%
“…and other related parameters are similar to those reported for electrochemically driven TCNQ/M-TCNQ solid-solid interconversion, where M is a group I (alkali metal), [39,40] group II (alkaline earth) [41,42] cation or first-row transition metal cation. [36,38,[43][44][45] On this basis, the observed voltammetry is attributed to the one-electron reduction of solid TCNQ 0 to TCNQ 1accompanied by rapid interaction with the [Pt(NH 3 ) 4 ] 2þ cation from the aqueous electrolyte at the TCNQ/TCNQ 1-(s) tGC (s) t[Pt(NH 3 ) 4 ](NO 3 ) 2(aq) triple-phase junction.…”
Section: Uv-vis Spectroscopymentioning
confidence: 97%